The feminist companion to mythology - Larrington, Carolyne (Pandora Press, 1992)
The mythology of the ancient Near East / Iris Furlong -- Egypt : myth and the reality / M.V. Seton-Williams -- The Hebrew God and his female complements / Athalya Brenner -- Greece / Barbara Smith -- Slav mythology / Julia Vytkovskaya -- Celtic goddesses : myths and mythology / Juliette Wood -- Scandinavia / Carolyne Larrington -- Mythology of the Eskimos / Birgitte Sonne -- Indian myth / Emily Kearns -- Chinese myths and legends / Tao Tao Liu -- Australian Aboriginal myth / Isobel White & Helen Payne -- M#ori mythology / Margaret Orbell -- Hawaii / Elizabeth Diab -- Southwest Native American mythology / Marta Weigle -- Mexican mythology / Susanna Rostas -- South America : the interpretation of myth / Penelope Harvey -- Witchcraft as goddess worship / Rosemary Ellen Guiley -- On psychic activism : feminist mythmaking / Jane Caputi -- Women's rewriting of myth / Diane Purkiss